2022
DOI: 10.1002/poc.4335
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of electrons trapped in cryogenic matrices with benzophenone

Abstract: The benzophenone radical anion 2 was generated by reaction of electrons with benzophenone 1 in argon and water matrices at cryogenic temperatures. Sodium as source of the electrons was co‐deposited with 1 in argon or in low‐density amorphous (LDA) water ice matrices. In solid argon, sodium atoms, 1, and small quantities of the radical anion 2 were observed after deposition. Visible light irradiation of these matrices resulted in an electron transfer from sodium to 1 under formation of the radical anion 2. If L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…Addressing the issues mentioned earlier, polycyclic aromatic hydrocarbons (PAHs; Figure 1a) were chosen as dopants due to their highly conjugated molecular structure and potential for phosphorescence emission, as evidenced in previous studies 27,[35][36] . The matrix chosen to construct the RTP materials with ultra-long afterglow was the benzophenone (BPO) and its derivative (MeBPO) (Figure 1a), which known for its ability to extract electron from other compounds [37][38][39] . The experimental outcomes confirmed that the resultant RTP materials displayed strong phosphorescence with varying colors and duration times.…”
Section: Introductionmentioning
confidence: 99%
“…Addressing the issues mentioned earlier, polycyclic aromatic hydrocarbons (PAHs; Figure 1a) were chosen as dopants due to their highly conjugated molecular structure and potential for phosphorescence emission, as evidenced in previous studies 27,[35][36] . The matrix chosen to construct the RTP materials with ultra-long afterglow was the benzophenone (BPO) and its derivative (MeBPO) (Figure 1a), which known for its ability to extract electron from other compounds [37][38][39] . The experimental outcomes confirmed that the resultant RTP materials displayed strong phosphorescence with varying colors and duration times.…”
Section: Introductionmentioning
confidence: 99%
“…However, the photoexcitation of radical anion 2 yielded back benzophenone 1 after losing an electron to the matrix. [1]…”
mentioning
confidence: 99%